Evaluation of screw pull-out from plate fixation of en bloc distal radius resection with ulnar reconstruction: Finite element analysis and comparison with experiments on Thiel cadavers - Wares Chancharoen; Theingi Nwe; Saran Seehanam; Napawan Taradolpisut; Thewarid Berkband; Thanapon Chobpenthai; Chavin Jongwannasiri; Laphatrada Yurasakpong (APL Bioengineering, 2025)
Fractures of the distal radius often require surgical intervention, with plate fixation being a standard stabilization method. Screw loosening and pull-out propose significant complications, necessitating comprehensive understanding of fixation stability factors. This study introduces a novel approach by the combination of finite element analysis (FEA) and experimental investigations on Thiel cadavers to evaluate screw pull-out behavior from plate fixation in en bloc distal radius resection with ulnar reconstruction. In comparison with previous investigations that used computational modeling or fresh-frozen cadaveric specimens, in the present research, FEA predictions specifically experimentally confirm the usage of Thiel cadavers, which better preserve soft tissue elasticity and hydration, thus more closely reflect in vivo conditions. Experimental set-up consisted of bending tests on cadavers and screw pull-out tests in Thiel-cadaveric radius specimens mimicking physiological conditions that induce the effects of screw pull-out. Finite element analysis and simulation were conducted using realistic clinical cases. Biomechanical test results indicated locking-plate deformation and screw loosening, particularly at locations closest to the ulnar bone gap. Torque measurements established various degrees of screw loosening, with the screws closest to the bone gap indicating maximum loosening. FEA demonstrated critical distributions of stresses in screws and locking plates, with good correlations to experimental findings. Screw pull-out force analysis showed vulnerability to loosening, particularly in the area of bone gaps, with findings consistent between biomechanical testing and FEA. This study offers valuable information on the surgical implications and biomechanical considerations of plate fixation for en bloc distal radius resection with ulnar reconstruction.